The Principle of Subsidiarity as a Constitutional Principle in the EU and Canada - Follesdal, Andreas; Muñiz Fraticelli, Victor (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique (CRÉ), 2015)
A Principle of Subsidiarity regulates the allocation and/or use of authority within a political order where authority is dispersed between a centre and various sub-units. Section 1 sketches the role of such principle of subsidiarity in the EU, and some of its significance in Canada. Section 2 presents some conceptions of subsidiarity that indicate the range of alternatives. Section 3 considers some areas where such conceptions might add value to constitutional and political deliberations in Canada. Section 4 concludes with some reminders of crucial contested issues not fully resolved by appeals to subsidiarity alone, exemplified by the protection of human rights.